Cardiovascular Prevention among Healthcare Professionals: the ESC Congress Cardiovascular Health Check 2025 - Florian A Wenzl; Yujing Wang; Virginia Mass; Frederik Filip Stæger; Mateusz Siedlinski; Mohan Satish; Cecilia Linde; Henning Bundgaard; Valentin Fuster; Tomasz J Guzik; Borja Ibáñez; Thomas F Lüscher (European Heart Journal, 2026)
Abstract Background and Aims Healthcare professionals (HCPs) play a central role in preventive care, yet their own cardiovascular health management remains poorly characterised. We evaluated cardiovascular risk profiles, awareness, treatment use, target achievement and subclinical atherosclerosis among HCPs attending the European Society of Cardiology (ESC) Congress. Methods HCPs participating in the ESC Congress Cardiovascular Health Check 2025 (n=1366) underwent standardised assessment of cardiovascular risk factors, medication use, treatment targets, and carotid ultrasonography in a subgroup. HCPs without established atherosclerotic cardiovascular disease (ASCVD) were compared with age- and sex-matched individuals from the general population (REACT initiative; n=2732). Results Among HCPs, excess body weight was the most prevalent modifiable risk factor (46.8%), followed by hypertension (23.2%), and hyperlipidaemia (22.7%). Established ASCVD was present in 11.1% and subclinical atherosclerosis was detected in 21.8% of HCPs without established ASCVD. Compared with matched controls, unrecognised hyperlipidaemia (7.5% vs. 8.4%; P=0.293), hypertension (11.9% vs. 13.9%; P=0.079), and diabetes (0.4% vs. 0.4%; P=0.864) were similarly frequent; awareness was higher only for hyperlipidaemia (62.2% vs. 54.9%; P=0.049). In primary prevention, HCPs were less likely to use recommended antihypertensive (27.6% vs. 46.5%; P<0.001) and glucose-lowering therapy (60.0% vs. 85.0%; P=0.001), but more often achieved LDL-C (57.5% vs. 32.0%; P<0.001) and systolic blood pressure targets (47.5% vs. 24.6%; P=0.003). In secondary prevention, 41.4% of HCPs used lipid-lowering therapy, only 9.2% used antiplatelet therapy, and only 22.2% of those using lipid-lowering therapy achieved the LDL-C target. Conclusions HCPs showed important gaps in cardiovascular prevention, particularly regarding the use of guideline-recommended therapy, highlighting the need for systematic implementation strategies among HCPs. Clinical Trial Registration: NCT07613229